PENGEMBANGAN DESAIN PEMBELAJARAN SISTEM BASIS DATA - Ruliah, Ruliah; Bahar, Bahar; Pratiwi, Andita Suci (Instruksional, 2021)
Instructional design plays an important role in improving the quality of learning and the learning experience of students. But in fact, many universities (especially in the field of Information Technology) have not developed a structured learning design, so that the learning process becomes ineffective. This paper presents a database system learning design model using the Borg and Gall step 1 development model and adapting all stages in the Dick and Carey model. The research consists of four main stages: conducting a preliminary study to find information about the learning product to be developed; develop products based on research findings; conduct field trials on the products developed; and revise products based on test results. The product quality of the developed learning design model is measured from aspects of validity and aspects of practicality. Validity is assessed through expert validation (database system learning material expert, instructional design expert, graphic media expert, and linguist). The measurement results obtained an average value of 5 (on a scale of 1-5), which means that the product of the learning design model developed is included in the valid category. Practicality is measured based on the responses of students and teachers. The results of the practicality measurement obtained an average value of 4.56 (on a scale of 1-5), which means that the product of the learning design model developed is included in the Practically used category